The Impact of Fraud on the Company’s Financial Statements - Cailah Nasywa Afrila; Dela Wahyu Putri Awanda; Hwihanus Hwihanus (International Journal of Economics, Commerce, and Management, 2024)
The purpose of this study is to identify methods to address financial statement fraud, both in developed and developing countries. Meta-analysis is a systematic statistical technique for combining several original studies in order to obtain more accurate and reliable results and conclusions. Through this approach, it is expected that ways to prevent government financial statement fraud can be identified, collected, and integrated. The analysis of 5 journals shows that some effective strategies to prevent financial statement fraud include good and effective internal controls, improving organizational culture, creating anti-fraud policies and procedures, and implementing forensic accounting.